BENEFÍCIOS E DIFICULDADES DA CERTIFICAÇÃO DO SELO DE EXCELÊNCIA ABCIC PELA PERSPECTIVA DOS GESTORES DE QUALIDADE - Ruiz, Phelipe Viana; Souza, Felipe Santos; Fontanini, Patricia Stella Pucharelli (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
One of the main productive sectors of the economy is the construction sector, characterized by a low productivity, caused by the lack of organization and control in the production, generating wastes of time and resources. Aiming at encouraging the implementation of quality, technology and performance improvements, quality seals have emerged, among them the "Selo de Excelência ABCICI". This study aims to identify the main difficulties to obtain that certification, the improvements in results and quality of service identified by the quality managers after obtaining the seal and if there are suggestions for improvement of the certification process. For this purpose, an online questionnaire was designed for quality sector managers of companies certified with the ABCIC Seal of Excellence of Levels I, II and III throughout Brazil. The results indicated that the main difficulties identified by the managers were related to the resistance of the employees, lack of training of the workers and little support from the top management. Among the benefits from certification, those with the greatest impact on the company were related to the greater visibility of the company with suppliers, better quality of production processes and internal management processes and greater competitive advantage and access to the market.